State-of-the-Art Materials and Spinning Technology for Hemodialyzer Membranes. Issue 3 (3rd July 2017) - Roy, Anirban; De, Sirshendu
Abstract : Hemodialysis provides the life support system for patients suffering from end-stage renal syndrome (ESRD). This review presents the historical development of different polymeric materials used for the synthesis of dialysis membranes. Initially, cellulose acetate and its derivatives formed the bases of polymeric materials for dialysis membranes, followed by polyacrylonitrile, polysulfone and others. The biocompatibility issues of each of these polymers have been discussed along with the clearance of uremic toxins. The acceptability of a particular membrane material for dialysis is not based entirely on the issue of biocompatibility. The uremic toxin flux is an equally important factor when recommending a particular material for use as a dialysis membrane. An ideal dialysis material would yield a membrane with high flux of uremic toxins with minimum biological reactions. Along with the development of biomaterials, spinning technologies employed for spinning of dialysis grade membranes have also been illustrated.